Manejo post cosecha del cultivo de cacao (Theobroma cacao) en la finca Meza ubicada en el recinto Pueblo Nuevo, cantón Babahoyo - Espin Vera, Rubi Jomaira (2019)
This work was developed at the Finca Meza, located on the road to Pueblo Nuevo, province of Los Ríos. Therefore, whose results support the writing of this monograph. The area has humid tropical climatic conditions, with an average annual temperature of 25.7 ºC. For the elaboration of this document, the literature review of several books, academic journals and the Internet, thesis and consultations to teachers of the agricultural and agricultural engineering school was developed, using theoretical level methods, such as interpretation and synthesis which allowed us to define our developed theme and finally it was concluded with a survey formed by questions regarding the research topic. As for the use of tools in the harvest, the machete is not convenient because it can hurt the floral cushions that will produce following fructifications and because it can produce cuts in the branches that favor the penetration of parasitic fungi to the tissues of the tree. The predominant fermentation system is in sacks for the advantage of being economical, however this is a rudimentary method that does not have daily removal does not allow the aeration of the dough which causes a lactic and butyric fermentation. In the post harvest it is observed that the predominant drying is in tendales, that although it is an economic method it has the disadvantage that it can easily be contaminated with dirt from car dust, waste from minor animals and plant residues. Cocoa almonds are stored fermented and dried in a warehouse on the farm where after the buyer has been found, they are transported to the collection center. Among the recommendations of this work is to use appropriate tools for the harvesting process, as well as almonds from healthy and ripe ears, to start the fermentation processes. Increase the infrastructure of drawers for the almond fermentation process. Carry out the natural drying process at the Meza farm by using slopes covered with chopped cane or a wooden floor. Make adjustments in the storage almond cellar, allocating an exclusive space only to store the almond.